2017
DOI: 10.1182/bloodadvances.2017009860
|View full text |Cite|
|
Sign up to set email alerts
|

Management of newly diagnosed immune thrombocytopenia: can we change outcomes?

Abstract: Immune thrombocytopenia resulting from antibody-mediated platelet destruction combined with impaired platelet production is a common cause of thrombocytopenia. The decision to treat newly diagnosed patients is based on several factors including ceasing hemorrhagic manifestations, increasing the platelet count, prevention of bleeding, and inducing remission.Current standard first-line therapy is a course of corticosteroids. Although this treatment paradigm increases the platelet count in the majority of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 50 publications
(43 reference statements)
0
47
0
4
Order By: Relevance
“…Rituximab is a chimeric monoclonal antibody targeting the B‐cell antigen CD20, approved for various malignant hematologic and rheumatologic disorders. It has shown efficacy in autoimmune hemolytic anemia, acquired coagulation factor deficiencies, thrombotic thrombocytopenic purpura, immune thrombocytopenic purpura (ITP), and has been used in other disorders such as antiphospholipid syndrome, and aplastic anemia, but its use in these non‐malignant immune‐mediated hematologic disorders is off‐label.…”
Section: Rituximabmentioning
confidence: 99%
“…Rituximab is a chimeric monoclonal antibody targeting the B‐cell antigen CD20, approved for various malignant hematologic and rheumatologic disorders. It has shown efficacy in autoimmune hemolytic anemia, acquired coagulation factor deficiencies, thrombotic thrombocytopenic purpura, immune thrombocytopenic purpura (ITP), and has been used in other disorders such as antiphospholipid syndrome, and aplastic anemia, but its use in these non‐malignant immune‐mediated hematologic disorders is off‐label.…”
Section: Rituximabmentioning
confidence: 99%
“…Previous long term studies showed that about 14% of children initially diagnosed with ITP were eventually diagnosed with other disorders like familial thrombocytopenia, systemic lupus erythematosus, Wiskott Aldrich syndrome etc. (3) or associated diseases (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Studii anterioare ce au urmărit pacienţii pe termen lung au arătat că aproximativ 14% dintre copiii la care iniţial trombocitopenia a fost interpretată în cadrul PTI au fost în final diagnosticaţi cu trombocitopenie familială, lupus eritematos sistemic, sindrom Wiskott Aldrich etc. (3) sau asociau şi alte afecţiuni (4,5).…”
Section: Materials şI Metodăunclassified